-19=-2(g-12)+-19

Simple and best practice solution for -19=-2(g-12)+-19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -19=-2(g-12)+-19 equation:


Simplifying
-19 = -2(g + -12) + -19

Reorder the terms:
-19 = -2(-12 + g) + -19
-19 = (-12 * -2 + g * -2) + -19
-19 = (24 + -2g) + -19

Reorder the terms:
-19 = 24 + -19 + -2g

Combine like terms: 24 + -19 = 5
-19 = 5 + -2g

Solving
-19 = 5 + -2g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '2g' to each side of the equation.
-19 + 2g = 5 + -2g + 2g

Combine like terms: -2g + 2g = 0
-19 + 2g = 5 + 0
-19 + 2g = 5

Add '19' to each side of the equation.
-19 + 19 + 2g = 5 + 19

Combine like terms: -19 + 19 = 0
0 + 2g = 5 + 19
2g = 5 + 19

Combine like terms: 5 + 19 = 24
2g = 24

Divide each side by '2'.
g = 12

Simplifying
g = 12

See similar equations:

| -19a+11a+19a-13a-3=-9 | | -46b-5=3b+9 | | 3h-h-12h+12=2 | | -16x+176=19x+1 | | 14x+9=7x+31 | | -3(x-7)+9x=6x+11 | | 4(6-y)+10=-10(y-2)-9 | | 3v+v-3v=9 | | 5=7-9 | | 8.425-3.143x=9.214x+12.081 | | a+7=-14 | | -42x-12=-6(6x-4) | | -13=12+m | | c=3+-3 | | -1+n=-20 | | -11x+10=-12x+8 | | 9x+3y+1y-0.9x= | | 10y-17=6y-12 | | -6x-10=38 | | 9x^2+18x-39=0 | | -10=h-6 | | -9+13x=11-x | | 5.39x+16=29.0521+4x | | 11-5x+3=2x+4-3x | | -13m+14-11=7(-m+13)+2 | | 15x+2=9x+22 | | 7(7y+17)=16+8(5y+5) | | 4x^5-22x^3-80x=0 | | -6p+7=-5(2p+13) | | 10(2)-3x=15 | | -16w=8(-w+6) | | r^2-2r^2+3r^2= |

Equations solver categories